Sulindac Compounds Facilitate the Cytotoxicity of β-Lapachone by Up-Regulation of NAD(P)H Quinone Oxidoreductase in Human Lung Cancer Cells - Kung, Hsiu-Ni; Weng, Tsai-Yun; Liu, Yu-Lin; Lu, Kuo-Shyan; Chau, Yat-Pang (PLOS ONE, 2014)
β-lapachone, a major component in an ethanol extract of Tabebuia avellanedae bark, is a promising potential therapeutic drug for various tumors, including lung cancer, the leading cause of cancer-related deaths worldwide. In the first part of this study, we found that apoptotic cell death induced in lung cancer cells by high concentrations of β-lapachone was mediated by increased activation of the pro-apoptotic factor JNK and decreased activation of the cell survival/proliferation factors PI3K, AKT, and ERK. In addition, β-lapachone toxicity was positively correlated with the expression and activity of NAD(P)H quinone oxidoreductase 1 (NQO1) in the tumor cells. In the second part, we found that the FDA-approved non-steroidal anti-inflammatory drug sulindac and its metabolites, sulindac sulfide and sulindac sulfone, increased NQO1 expression and activity in the lung adenocarcinoma cell lines CL1-1 and CL1-5, which have lower NQO1 levels and lower sensitivity to β-lapachone treatment than the A549 cell lines, and that inhibition of NQO1 by either dicoumarol treatment or NQO1 siRNA knockdown inhibited this sulindac-induced increase in β-lapachone cytotoxicity. In conclusion, sulindac and its metabolites synergistically increase the anticancer effects of β-lapachone primarily by increasing NQO1 activity and expression, and these two drugs may provide a novel combination therapy for lung cancers.